Spatial Assessment and the Most Significant Parameters for Drinking Water Quality Using Chemometric Technique: A Case Study at Malaysia Water Treatment Plants - M. Zolkipli, H; Juahir, H; Adiana, G; Zainuddin, N; Ismail, A; B. H. M. Maliki, A; I. Hussain, N; K. A. Kamarudin, M; E. Toriman, M; Mokhtar, M (International Journal of Engineering and Technology, 2018)
The objectives of this study are to determine the most significant spatial variation of drinking water pollutant and to identify the most significant parameters in each group of physico- chemical parameters (PCPs), Inorganic parameters (IOPs), heavy metals and organic parameters (HMOPs) and pesticides parameters (PPs). The Discriminant Analysis (DA) and One- Way Analysis of variance (ANOVA) showed spatial variation on four station categories and the variance of four group parameter in water drinking quality while principle component analysis (PCA) was carried out to identify the most significant of each water quality parameters base on given group. DA and ANOVA successfully reduced the physico and inorganic pollutants concentration with significant value 98.63% and 96.90%. PCA revealed six most significant drinking water quality parameters for PCPs, nine significant parameters for IOPs, fourteen parameters on HMOPs and four significant of PPs with the p value less than 0.05 (p < 0.05). Therefore, this study proves that chemometric method is the alternative way to explain the characteristic of the drinking water quality and could reduce several parameters and sampling points in the future sampling strategy.